Attitudes towards the usage of open educational resources by postgraduate students at the National Open University of Nigeria (NOUN), south-south Nigeria - Ambrose, Smart Eromosele; Akporhonor, Blessings A.; Njeze , Miracle Eka (Communicate: Journal of Library and Information Science, 2023)
This study examined the attitudes towards the usage of OER by postgraduate students in National Open University of Nigeria (NOUN), south-south, Nigeria. Thus was achieved using three hypotheses generated to guide the study. The study adopted the descriptive survey design type on a population of 2,119 postgraduate students. Using stratified random sampling techniques, 15% of the population (318) was used for the sample for the study. Questionnaire was used to elicit data from the respondents, and upon administration, a 95% response rate was achieved. The data was analysed using descriptive statistics (for the demographics) and inferential statistics (for the hypotheses).The findings revealed that the postgraduate students have a positive attitude towards the use of OER. The OER mostly used by postgraduate students includes learning modules and video streaming, lecture materials online, open courseware, e-book, syllabi, Open Access Electronic Thesis (OAET), open textbooks, open access journals and course videos/ YouTube. There was a gender difference among postgraduate students towards the use of OER but there was no significant difference in the utilization of OER by postgraduate students’ by faculties. The study also found that attitude has a significant influence on the usage of OER by postgraduate students. Based on the findings, the study concluded that to stimulate the use of OER among postgraduate students, their awareness and attitude would have to be positively triggered.